2023
DOI: 10.3390/medicina59030502
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic Evaluation of the Gap between Cemented Post and Remaining Gutta-Percha in Endodontically Treated Teeth Performed by Undergraduate Students: A Retrospective Cross-Sectional Study

Abstract: The coronal seal in root canal-treated teeth may be compromised depending on the accuracy of post space preparation and post cementation along with remaining gutta-percha. Root canal treatment can be compromised by endotoxins released by the coronal bacteria as a result of microleakage. The study was conducted by undergraduate students to measure the gap between the cemented post and residual gutta-percha. In total, 217 endodontically treated teeth were evaluated with intraoral peri-apical radiographs. Based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…Maxillary incisors were the most common type of teeth included in this study, followed by premolars. This observation is consistent with some of the previous studies [ 2 , 13 ]. Different order was observed in other studies where premolars were the most restored teeth followed by anteriors [ 3 , 5 , 15 ].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Maxillary incisors were the most common type of teeth included in this study, followed by premolars. This observation is consistent with some of the previous studies [ 2 , 13 ]. Different order was observed in other studies where premolars were the most restored teeth followed by anteriors [ 3 , 5 , 15 ].…”
Section: Discussionsupporting
confidence: 94%
“…A study performed by Meshni et al [ 12 ] showed similar results, and the remaining GP was 3-5 mm in 55% and >5 mm in 29% of the treated cases. Other studies reported more than two-thirds of the cases achieved suboptimum (>5 mm), while around one-third showed optimal measurments (3-5 mm) of remaining apical GP [ 2 , 3 , 13 ]. These differences could be related to sample heterogenecity between the studies, including type of teeth included and students' academic levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Advancements in biomaterials and surgical techniques allow for treatments that are tailored to the unique needs and conditions of each patient. This individualized approach is crucial, especially in complex cases where a standardized treatment may not suffice [ 2 ]. Furthermore, the exploration of new frontiers, such as the use of ozonated water for the treatment of Candida infections, represents a significant step towards finding more effective, safer, and less invasive treatment options.…”
mentioning
confidence: 99%
“…The same participants were divided into three groups as well, in order to determine how much gutta-percha was still present after the post-and core-procedure [10,[20][21][22].…”
mentioning
confidence: 99%